Pedro Pablo Ccopa, La cocina de acogida. Migrantes andinos en Lima: memorias, sabores y sentidos, Lima, USMP, 2018 (176 páginas) - Martuccelli, Danilo (2019)
Pedro Pablo Ccopa's new book, La Cocina de Acagida, is a particular book within the author's own trajectory and the perspective he has been developing for years on Lima society, but it is also an important book, due to the novelty of the perspective that encourages it, within Peruvian sociology.